THE EFFECT OF SERVICE EXPERIENCE AND DIGITAL ENGAGEMENT STRATEGIES ON REPURCHASE INTENTION WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE (STUDY ON LATEN COFFEE AND FOODS) - Kristanti, Nathania; Lapian, S. L. H. V. Joyce; Tawas, Hendra N. (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
In the increasingly competitive coffee market, a deep understanding of factors such as service experience and digital engagement strategies that influence customer satisfaction and consumer decisions to repurchase (repurchase intention) is crucial for coffee companies. This study aims to analyze the direct influence of service experience and digital engagement strategies on customer satisfaction and repurchase intention as well as the indirect influence of service experience and digital engagement strategies on repurchase intention through customer satisfaction at Laten Coffee and Foods. Data collection was carried out by distributing questionnaires to 100 respondents using the Path Analysis technique. The results of this study indicate 1) Service Experience has a direct positive and significant effect on Customer Satisfaction. 2) Digital Engagement Strategies have a direct positive and significant effect on Customer Satisfaction. 3) Service Experience has a direct positive and significant effect on Repurchase Intention. 4) Digital Engagement Strategies have a direct positive and significant effect on Repurchase Intention. 5) Customer Satisfaction has a direct positive and significant effect on Repurchase Intention. 6) Service Experience has a positive and significant indirect effect on Repurchase Intention through Customer Satisfaction as an intervening variable. 7) Digital Engagement Strategies do not have a significant indirect effect on Repurchase Intention through Customer Satisfaction as an intervening variable.